Angus, thongs and full-frontal snogging : confessions of Georgia Nicolson / 1. - Rennison, Louise (Confessions of Georgia Nicolson, 2000)
Presents the humorous journal of a year in the life of a fourteen-year-old British girl who tries to reduce the size of her nose, stop her mad cat from terrorizing the neighborhood animals, and win the love of handsome hunk Robbie.